Ptosis effects on intraocular lens power calculation. Issue 2 (February 2023) - Aydemir, Emre; Aksoy Aydemir, Gozde
Abstract : Decreased corneal keratometry values were observed in all the ptosis patients, and a decrease of 0.50 D was observed in the CA value in droopy eyelids >4 mm. Abstract : Purpose: To evaluate quantitatively ocular biometric parameters and intraocular lens (IOL) power measurements after ptosis surgery. Setting: Adiyaman University Hospital, Adiyaman, Turkey. Design: Comparative prospective clinical study. Methods: This study comprised involutional ptosis patients divided into droopy eyelid severity groups: Group 1: >4 mm, Group 2: 3 to 4 mm, and Group 3: 1 to 2 mm. The patients underwent anterior levator resection, and preoperative and postoperative biometry measurements at 3 months postoperatively were obtained. Results: The Group 1 sample size was 19, Group 2 was 22, and Group 3 was 16. The mean flattest keratometry (K1 ), steepest keratometry (K2 ), and mean keratometry (Km ) values significantly decreased at 3 months postoperatively in Group 1 ( P < .001 for all). The mean K1, K2, and Km values nonsignificantly decreased at 3 months postoperatively in Groups 2 and 3 ( P > .05 for all). The mean corneal astigmatism magnitude decreased at 3 months postoperatively in Group 1 ( P < .01), Group 2 ( P = .186), and Group 3 ( P = .952). The mean recommended IOL powers targeting emmetropia increased postoperatively in Group 1 and were similar preoperatively and postoperatively in Groups 2 and 3. In Group 1, the mean changes after ptosis surgery by the formula were 0.47 diopters (D) for SRK/T, 0.52 D for Hoffer Q, 0.55 D for Haigis, 0.50 D for Barrett Universal II, and 0.55 D for Holladay 2. Conclusions: Ptosis >4 mm significantly affects corneal curvature values and IOL power calculations when cataract surgery is planned. Surgeons might consider altering their lens power choice accordingly if cataract surgery is to be sequentially followed by ptosis repair.